Effectiveness of Implementing Islamic Values in General Subjects at SDIT Cahaya Insani Parakan Temanggung District: Efektifitas Penanaman Nilai-Nilai Islam dalam Mata Pelajaran Umum di SDIT Cahaya Insani Parakan Kabupaten Temanggung - Wahyuni, W; Mawardi, Imam (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
The aim of this research is to determine the extent to which teachers can apply the basic values of Islamic teachings in general subjects so that it will strengthen students' understanding of Islamic teachings at SDIT Cahaya Insani Parakan Temanggung. This research uses descriptive qualitative research. Respondents in this study were school principals, deputy school principals and teachers. The data collection techniques used were observation and interview methods. Data analysis carried out was data presentation and verification of observations and interviews. The results of this research are that teachers' skills in implementing the instillation of Islamic values in learning begin to be carried out with good collaboration between the principal and teachers, teachers and teachers who try to develop good teaching quality and make it easier for teachers to manage the class. In instilling Islamic values in general subjects, teachers must hone the basic Islamic sciences so that the Islamic values that are applied become stronger.